2015
DOI: 10.1016/j.celrep.2015.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Individual Stromal Cell Populations Identifies Stroma-Tumor Crosstalk in Mouse Lung Cancer Model

Abstract: Emerging studies have begun to demonstrate that reprogrammed stromal cells play pivotal roles in tumor growth, metastasis, and resistance to therapy. However, the contribution of stromal cells to non-small-cell lung cancer (NSCLC) has remained underexplored. We used an orthotopic model of Kras-driven NSCLC to systematically dissect the contribution of specific hematopoietic stromal cells in lung cancer. RNA deep-sequencing analysis of individually sorted myeloid lineage and tumor epithelial cells revealed cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 50 publications
2
130
1
Order By: Relevance
“…In pancreatic cancer with its large collagen deposits, a worse prognosis was found in patients with high intratumoral stromal activity, defined by high α-SMA activity together with low collagen deposition (12). However, NSCLC appears to have a clearly different stromal composition (6,24), and the activated stroma index was not confirmed as a significant prognostic factor in the present study.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In pancreatic cancer with its large collagen deposits, a worse prognosis was found in patients with high intratumoral stromal activity, defined by high α-SMA activity together with low collagen deposition (12). However, NSCLC appears to have a clearly different stromal composition (6,24), and the activated stroma index was not confirmed as a significant prognostic factor in the present study.…”
Section: Discussioncontrasting
confidence: 90%
“…NSCLC has distinct histopathological characteristics. Tumor-stroma interactions and the tumor microenvironment play an important role; however, the most relevant candidate markers and paracrine or autocrine crosstalk pathways appear to be different from those known for pancreatic cancer (6,24). …”
Section: Discussionmentioning
confidence: 99%
“…Using an orthotopic Kras-driven NSCLC mouse model ( K-ras LSL-G12D/+ ;p53 flox/flox ), we have evaluated the differential gene expression in epithelial and intratumoral stromal cells by RNA-seq analysis [18]. Interestingly, we found that MMP14 was significantly upregulated both in intratumoral myeloid cells (CD11b + F4/80+ macrophages, Ly6C+ monocytes, Ly6G+ neutrophils) and EpCam + tumor cells (Figure 1 A and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The Kras -driven lung tumor microenvironment consists of diverse immune cells (34). Kras -driven 344SQ mouse tumors are metastatic and associated with fewer infiltrating CD8 + T cells in the tumor (21).…”
Section: Discussionmentioning
confidence: 99%